Relations Between Dimensions of Emotional Intelligence, Specific Aspects of Empathy, and Non-verbal Sensitivity - Fernández-Abascal, Enrique G.; Martín-Díaz, María Dolores (Frontiers in Psychology, 2019)
In this work, on the one hand, we examined the relationship between emotional intelligence (EI) and empathy and, on the other, the relationship between emotional intelligence and nonverbal sensitivity, through two independent studies. The first study analyzed the relationship between dimensions of emotional intelligence and aspects of empathy, in a sample of 856 participants who completed two measures of EI, the Trait Meta-Mood Scale (TMMS) and the Trait Emotional Intelligence Questionnaire (TEIQue), and a measure of empathy, The Interpersonal Reactivity Index (IRI). The results showed a similar pattern of significant positive relations in all the EI domains with empathic Perspective-taking, and significant negative relationships with empathic Personal Distress, except for the EI domain of Attention, which had a positive relationship. Stepwise multiple regression analyses showed that the dimension that best predicted empathic Perspective-taking and Empathic Concern was the Emotionality Factor; whereas Attention best predicted empathic Fantasy; and the Self-Control Factor best predicted Personal Distress, although negatively. Gender emerged as a predictor of three empathic aspects, Fantasy, Empathic Concern, and Personal Distress, with women obtaining higher scores than men in all of them. Age was the only predictor of Fantasy, with a negative relationship. The second study involved 646 people who completed the same measures of EI as the participants of the first study and the Mini-Profile of Nonverbal Sensitivity (Mini-PONS). The results showed some significant relationships between EI dimensions and the channels and quadrants of the MiniPONS. Stepwise multiple regression analyses showed that very few EI dimensions predicted nonverbal sensitivity, with Attention obtaining the best result. Both gender and age emerged as predictors, some in unique cases, of channels, quadrants and of the total score of nonverbal sensitivity; age had a negative relationship, and women obtained higher scores than men.